Anomic Dependence and Corruptive Contagion. Regulatory Hypercomplexity and Social Fragmentation in the Mid-Global Era - Rufino, Annamaria (Italian Sociological Review, 2022)
Corruption is normally perceived as a system of power that overlaps the state-system. The average citizen seems subjugated to its workings and refrains from fighting against it. The reasons of such an attitude could be subjected to different explanations; there is no doubt that, generally, the social actors consider the state apparatus and its institutions responsible for their lack of action in the face of a widespread practice of corruption, within society. Another relevant aspect is that, due to the transversal nature of corruption, all its proceedings seem to swallow the root of the practice, namely the first corrupted act. As consequence of that, corruption, as a phenomenon, seems to operate as a spiderweb, from which it becomes difficult to untangle.